2021
DOI: 10.3390/dj9010005
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of Primary Stability Values for Two Differently Designed Implants to Suit Immediate Loading in Very Soft Bone

Abstract: The achievement of sufficient implant stability in poor quality bone seems to be a challenge. Most manufacturers develop special dental implants, which are claimed to show higher stability even in very soft bone. The aim of this experimental study was to compare two recently introduced dental implants with differing thread designs. A total of 11 implants of each group were inserted in the part of the fresh bovine ribs, corresponding to very soft bone. The primary stability was measured with resonance frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A recently introduced progressive-type two-piece implant (PL) combines different thread designs spanning from the upper parallel segment down to the apex of the lower tapered segment. In vitro data have indicated that this particular implant design was associated with adequate primary stability values in a very challenging type-4 bone model [ 9 ], thus suggesting its suitability for immediate protocols.…”
Section: Introductionmentioning
confidence: 99%
“…A recently introduced progressive-type two-piece implant (PL) combines different thread designs spanning from the upper parallel segment down to the apex of the lower tapered segment. In vitro data have indicated that this particular implant design was associated with adequate primary stability values in a very challenging type-4 bone model [ 9 ], thus suggesting its suitability for immediate protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to some in vitro and cadaver studies [5,6,22,26,44], the implant site under-preparation is able to significantly improve not only the IT and RFA, but also the implant PS in low-quality bone. Moreover, in preparing dental implant osteotomies, it was revealed that a low-speed drilling without irrigation has been comparable to conventional drilling [45].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that implant osseointegration is a continuous biological process involving constant bone remodeling [14], in vitro studies encountered challenges in accurately reproducing the clinical scenario. An in vitro study using bovine ribs from Krischik et al [15] evaluated different implant designs and the implant site preparation for obtaining primary stability, and both factors influenced the results. Flanagan et al [16] evaluated the horizontal force required to move non-osseointegrated implants in bovine mandibles in vitro, concluding that there is a need to control occlusal forces during implant healing.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study using bovine ribs from Krischik et al. [15] evaluated different implant designs and the implant site preparation for obtaining primary stability, and both factors influenced the results. Flanagan et al.…”
Section: Introductionmentioning
confidence: 99%